Characterizing Photosymbiosis Between Fraginae Bivalves and Symbiodinium Using Phylogenetics and Stable Isotopes - Li, Jingchun; Volsteadt, Megan; Kirkendale, Lisa; Cavanaugh, Colleen M. (Frontiers in Ecology and Evolution, 2018)
Photosymbiotic associations between heterotrophic hosts and photosynthetic algae play crucial roles in maintaining the trophic and structural integrity of coral reef ecosystems. The marine bivalve subfamily Fraginae contains both non-symbiotic and photosymbiotic lineages, making it an ideal comparative system to study the origin and evolutionary adaptations of photosymbiosis. The symbiotic species exhibit unique morphological adaptations to photosymbiosis. However, the basic biology of these photosymbiotic relationships, such as symbiont diversity and nutritional benefits, has not been thoroughly characterized. In this study, we examined the general morphology of four Fraginae species occupying different depths (0-10 meters): Corculum cardissa, Fragum fragum, Fragum scruposum, and Fragum sueziense. Abundant symbionts were found in the mantle, gill, and part of the foot, contained in tubular networks within host tissues. We used molecular phylogenetics to investigate the algal symbiont communities of these Fraginae species. Results showed that symbionts from all four species are dinoflagellates belonging to the Symbiodinium clade C and we did not detect any host-specific or geographic-specific genetic structures with in the symbionts. We also used stable carbon isotope analyses to examine whether the cockles are directly utilizing photosynthetically derived carbon sources. All species show less depleted C13 compared to filter-feeding bivalves, suggesting at least part of their organic carbon is derived directly from the symbionts. However, C13 depletion of Fragum sueziense collected from deeper habitats are less distinguishable from filter-feeding bivalves. This indicates that species in deeper habitats may rely less on photosymbiosis due to the reduced light availability. Given that the symbiotic fragines exhibit varying morphologies, habitats, and utilization of symbiont photosynthesis, the subfamily represents an ideal model system to study differential adaptations to photosymbiosis.